THE ROLE OF PARENTS IN IMPROVING THE LEARNING ACHIEVEMENT IN SLOW LEARNER STUDENTS IN ELEMENTARY SCHOOL - Hutasoit, Enjelina; Slameto (EZRA SCIENCE BULLETIN, 2024)
This literary research investigates parents' significant role in enhancing elementary school students' learning achievement, mainly focusing on slow learners. Slow learners often face unique challenges in academic progress, requiring tailored support from educators and parents. Through a comprehensive review of existing literature, this study examines various strategies and interventions parents employ to facilitate their children's learning outcomes. The research also explores the effect of parental involvement, communication, and support on slow learners' knowledge performance and overall well-being. By synthesizing findings from diverse scholarly sources, this paper aims to provide insights into effective parental practices that can positively influence the educational journey of elementary school students with learning difficulties.